The governance of disease outbreaks: international health law: lessons from the Ebola crisis and beyond - Vierck, Leonie; Villarreal, Pedro A.; Weilert, A. Katarina (Nomos Verlagsgesellschaft mbH & Co. KG, 2017)
This edited volume is directed at experts in international law, practitioners in international institutions, and other experts who would like to familiarize themselves with the legal framework of infectious disease governance. Using the West African Ebola crisis as a case study, this book is part of a larger collaborative project on international health governance. Project partners are the Forschungsstätte der Evangelischen Studiengemeinschaft e.V. - Institute for Interdisciplinary Research and the Max Planck Institute for Comparative Public Law and International Law (MPIL). The authors explain the context and substantive legal framework of the Ebola crisis, while also highlighting its human rights aspects, institutional law (such as the debate on the securitization of health), and the limits to a purely legal approach to the subject. The authors are experts in public international law, public health, political science, and anthropology. With contributions by: Elif Askin, Susan L. Erikson, André den Exter, Robert Frau, Wolfgang Hein, Bonnie Kaiser, Hunter Keys, Michael Marx, Edefe Ojomo, Ilja Richard Pavone, Mateja Steinbrück Platise, Christian R. Thauer, Leonie Vierck, Pedro A. Villarreal, A. Katarina Weilert. Der Sammelband richtet sich an ein Fachpublikum von Völkerrechtlern, Praktikern in internationalen Institutionen und anderen Experten, die sich mit den rechtlichen Rahmenbedingungen der internationalen Governance ansteckender Krankheiten vertraut machen möchten. Fallbeispiel ist die Ebola-Krise in Westafrika. Der Band geht aus einem breiter angelegten Heidelberger Kooperationsprojekt zur „International Health Governance“ der Forschungsstätte der Evangelischen Studiengemeinschaft e.V. - Institut für interdisziplinäre Forschung (FEST) und des Max-Planck-Instituts für ausländisches öffentliches Recht und Völkerrecht (MPIL) hervor. Die Autoren beleuchten Kontext und materiellen Rechtsrahmen des Themas, auch unter Hervorhebung menschenrechtlicher Bezüge, institutionelles Recht („Gesundheit als Sicherheitsrisiko?“) sowie die Grenzen eines genuin rechtlichen Ansatzes. Die Autoren sind den Disziplinen Völkerrecht, Public Health, Politikwissenschaften und Anthropologie zuzuordnen. Mit Beiträgen von: Elif Askin, Susan L. Erikson, André den Exter, Robert Frau, Wolfgang Hein, Bonnie Kaiser, Hunter Keys, Michael Marx, Edefe Ojomo, Ilja Richard Pavone, Mateja Steinbrück Platise, Christian R. Thauer, Leonie Vierck, Pedro A. Villarreal, A. Katarina Weilert